Effect of Refractance Window™ and oven drying on physicochemical and sensory properties of peach (Prunus persica L.) surplus - Largo-Avila, Esteban; Rico-Rodríguez, Fabián; Peñaloza-Figueroa, Jeanine Kathleen; López-Padilla, Alexis (Frontiers in Nutrition, 2024)
Currently, approximately 34% of fruit is lost and wasted in emerging economies due to inefficient post-harvest processes, technological shortcomings, lesser valorisation of surpluses and byproducts. One way to take advantage of this type of product is through the application of drying processes that increase its shelf life and its inclusion in the food chain. Refractance Window Drying (RWD) is a 4th generation drying technique implemented by the food industry in the last few decades and has been applied to several dehydrated food products. This study compared the effects of different drying methods on the physical and sensory properties of surplus Colombian peaches. Treatments consisted of (i) peaches were sliced (1, 2, and 3 mm thick) and dried using either RWD at 86°C, (ii) peach pulp mixed with maltodextrin (MD) (0.12 - 0.33 kg of MD/kg of sample) and RWD (RWD-MD), and (iii) conventional oven drying (OD) at 60°C (3 mm thick) dried for 24 hours. The study found that the drying method significantly (p<0.05) affected the peaches' texture, color, and general taste. The results showed that processing treatments combined with different drying conditions affected the physical properties of the peach. RWD in slices reduced water content to until 0.05 kg H2O/kg in 40 min, showing fewer effects on color attributes. A surface response analysis on RWD showed good correlations for water activity (R2= 0.8652 – 0.9894) and moisture content (R2= 0.7048 - 0.9826). A higher diffusion coefficient (1.63×10-6 m2⋅s-1) was observed for RWD in slices with 3×10-3 m of thickness; however, for RWD-MD, differences in diffusion coefficients were present for the lowest MD addition (0.12 kg/kg), vitamin C was not detected on the dried slices and higher concentration of β-carotene (175.88 μg/100 g) were found on the thinner slices. Principal Component Analysis showed that RWD in the slices was the most suitable drying process, followed by OD. Sensory analysis showed good acceptability for RWD slices after 30 days of storage.